1976
DOI: 10.2307/1239263
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Gain Isoquants and a Decision Model Application for Swine Production

Abstract: Historic estimates of livestock production functions have used repeated observations on the animals to estimate the overall gain surface. The estimates involve autocorrelation accordingly. To circumvent this problem, gain isoquants are estimated directly by means of an instrumental variable approach. Data are from a swine experiment designed for the purpose with 648 hogs. Protein supplement and corn serve as the substitute inputs. Protein supplement is estimated as the instrumental variable. Isoquant equations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1980
1980
2006
2006

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…When examined according to the maturity stage of a pig of given genotype, the optimal precision feeding pattern is generally in line with the results of previous studies (Dent et al 1970, Sonka et al 1976, Glen 1983, Chavas et al 1985. The degree of adjustment during the fattening period is, however, larger in this study than in similar studies.…”
Section: Management Implicationssupporting
confidence: 90%
See 3 more Smart Citations
“…When examined according to the maturity stage of a pig of given genotype, the optimal precision feeding pattern is generally in line with the results of previous studies (Dent et al 1970, Sonka et al 1976, Glen 1983, Chavas et al 1985. The degree of adjustment during the fattening period is, however, larger in this study than in similar studies.…”
Section: Management Implicationssupporting
confidence: 90%
“…These results, however, do not permit the construction of a continuous growth curve. Sonka et al (1976), observed a similar change in the feeding pattern as the pig grows. They estimated that the optimal share of protein in the diet varies between 12-18% depending on the growth stage of the animal as well as on input prices.…”
Section: Choosing the Optimal Feeding Patternsmentioning
confidence: 63%
See 2 more Smart Citations
“…See Perrin (1972) for further extensions of the importance of the time variable in the decision process. For a different approach using time in production functions, swine analyses are presented by Dahm et al (1976) and Sonka et al (1976). These authors implicitly incorporate time in their production functions.…”
Section: Methodsmentioning
confidence: 99%